Commune development planning process for decentralized rural development in Cambodia : a case study of Srayov Commune - Chin Sosamphors; Routray, Jayant Kumar; Soparth Pongquan; Ahmad, Mokbul Morshed; Sweden (Sida) (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
Since the Commune Council (CC) election in February 2002, the elected CC officials have been challenged to put into practice the decentralization policies mandated by the national government. This includes not only administrative reform but also involvement in development planning and implementation of the projects. Realistically, the CC needs time to fully perform the roles expected of them. Nevertheless, progress has already been made in several aspects of the decentralization process, especially by CC that has received more intensive support from government programs and external organizations. The research deals with the Commune Development Planning Process (CDPP) for Decentralized Rural Development (DRD) that involves in 11 steps of commune development planning process following by guideline of Ministry of Interior undertaken in planning and implementing development projects. Identification of the problems associated in planning process and implementation which some key aspects were analyzed are constrains of participation in the process, the roles of PBC involved in planning facilitator in the CDP. Partnership of the CC with civil society and national government in commune development planning process and working relationships in the projects implementation. The research was conducted in the Srayov commune in Kampong Thom province using a checklist for officials of PoLA, PFT, DFT, NGOs and CC's members. Group discussions were conducted with VDCs, villages' headman, gender representative and villagers. In addition to the secondary data related documents, reports, manuals, guidelines and commune law, Prakas (law), and Sub-decrees were collected from Cambodia Development Council (CDC), DoLA, as well as NGOs and others. The research is based on qualitative analysis. The study concludes that the early experience of the CC offered much enthusiasm for broad based support of the decentralization reform program. While progress to date has been uneven and less than inclusive, much has been achieved in a relatively short period of time. Certain key recommendations are made for CC and relevant government agencies to enhance the decentralized planning of CC. These are focused on the CC leading to increased local ownership and participation with key stakeholders to be effective in the long-term, CC handling infrastructure projects to address pressing community issues.
A research study submitted in partial fulfillment of requirement for the degree of Master of Science in Regional and Rural Development Planning
Research Studies Project Report (M.Sc.) - Asian Institute of Technology, 2007
Keywords: Rural development -- Cambodia; Decentralization -- Cambodia; Communal living -- Cambodia